Internet of things in construction industry revolution 4.0: Recent trends and challenges in the Malaysian context - Gamil Y.; A. Abdullah M.; Abd Rahman I.; Asad M.M. (Emerald Group Holdings Ltd., 2023)
Construction industry; Embedded systems; Industrial research; Internet of things; Surveys; Construction projects; Design/methodology/approach; Industrial challenges; Industrial revolutions; Internet of thing (IOT); Malaysian construction industry; Quantitative research; Questionnaire surveys; Industrial internet of things (IIoT)